An exploration of balance and skill in the jump shot - Spina, M. S.; Cleary, T. D.; Hudson, J. L. (ISBS - Conference Proceedings Archive (Konstanz), 1995)
The jump shot is the primary offensive weapon in basketball, and accuracy is critical to success. In free throw shooting, accuracy has been associated with low horizontal mobility and high stability (Hudson, 1985). In jump shooting, low mobility is desirable for avoiding fouls, but high stability may be counter-productive to achieving a good jump. That is, a large, stable base of support is less effective for jumping than a smaller base on the balls of the feet. How do jump shooters resolve this apparent conflict between high stability for accuracy and low stability for good jumps? Opting for low stability may be problematic if, according to the generally inverse relationship between stability and mobility, it leads to high mobility. And any solution in the anteroposterior plane can be threatened by instability in the mediolateral plane. Given these complexities of choice in the components of balance, players of diverse abilities may adopt different strategies. The purpose of this study was to explore how advanced and intermediate performers regulate balance in the jump shot.